2017
DOI: 10.1139/cjfas-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Temporally stable, weak genetic structuring in brackish water northern pike (Esox lucius) in the Baltic Sea indicates a contrasting divergence pattern relative to freshwater populations

Abstract: Understanding spatiotemporal population genetic patterns is important for conservation management of ecologically and socioeconomically important species. This is particularly so in species-poor environments such as the brackish Baltic Sea. We examined over 600 northern pike (Esox lucius), a coastal predator and treasured sport fish, collected over major parts of the Baltic Sea coastline. We found low genetic divergence among populations, indicating a contrasting genetic structure of brackish water coastal spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 60 publications
5
32
2
Order By: Relevance
“…Genetic monitoring over years within single decades shows a temporally stable structure and amount of genetic variation in pike, plaice, cod, and three‐spined stickleback (DeFaveri & Merilä, ; Pampoulie, Stefánsson, Jörundsdóttir, Danilowicz, & Daníelsdottír, ; Was, Gosling, & Hoarau, ; Wennerström et al, ), but with some temporal differences observed in turbot (Nielsen, Nielsen, Meldrup, & Hansen, ). Within‐season genetic differences at herring spawning sites are interpreted as genetically different populations using the same spawning grounds (spawning waves; Jørgensen, Hansen, Bekkevold, Ruzzante, & Loeschcke, ; Jørgensen, Hansen, & Loeschcke, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic monitoring over years within single decades shows a temporally stable structure and amount of genetic variation in pike, plaice, cod, and three‐spined stickleback (DeFaveri & Merilä, ; Pampoulie, Stefánsson, Jörundsdóttir, Danilowicz, & Daníelsdottír, ; Was, Gosling, & Hoarau, ; Wennerström et al, ), but with some temporal differences observed in turbot (Nielsen, Nielsen, Meldrup, & Hansen, ). Within‐season genetic differences at herring spawning sites are interpreted as genetically different populations using the same spawning grounds (spawning waves; Jørgensen, Hansen, Bekkevold, Ruzzante, & Loeschcke, ; Jørgensen, Hansen, & Loeschcke, ).…”
Section: Resultsmentioning
confidence: 99%
“…Delimitation of population genetic structure in order to identify more or less isolated populations is of importance to define management units. Such information exists for fish species including Atlantic salmon (Salmo salar; Koljonen, Jansson, Paaver, Vasin, & Koskiniemi, 1999;Säisä et al, 2005), northern pike (Esox lucius; Laikre, Miller, et al, 2005;Wennerström et al, 2017), whitefish (Coregonus lavaretus; Olsson, Florin, Mo, Aho, & Ryman, 2012) and for habitat forming species such as bladderwrack (Fucus vesiculosus; Johannesson, Johansson et al, 2011). Also, identification of local adaptations is of particular importance in variable environments such as that of the Baltic Sea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, declines in pike populations in the Baltic Sea have been observed during the last decades (Lehtonen et al, 2009;Ljunggren et al, 2010;Nilsson et al, 2019;Olsson, 2019), and management actions, e.g., restoration of spawning habitats, have therefore been conducted to support the populations (Larsson et al, 2015). Population assignments that could be used to aid in decisions concerning such management efforts have mainly been based on studies utilizing neutral microsatellite markers Wennerström et al, 2016;Eschbach et al, 2019;Nordahl et al, 2019).…”
Section: Study Speciesmentioning
confidence: 99%